Fahr’s disease in an older adult: a geriatric view - Damián-Mucha, Milagros (2025)
Fahr’s disease is an unusual condition, characterized by bilateral and symmetrical intracranial calcifications. We present the case of a 75-year-old man, who was admitted to the emergency room due to a biliary obstruction following a periampullary neoplasm. During his stay, the patient fell after an episode of psychomotor agitation without apparent cause; therefore, it led to a computed tomography (CT) scan of the brain, which revealed bilateral calcified lesions in the basal nuclei and globus pallidus. The disease was managed exclusively, but there were shortcomings in the integrated approach to the older adult. Subsequently, during the comprehensive geriatric assessment, it was detected that the was a frail elderly patient, with acquired deconditioning, malnutrition, social vulnerability, and caregiver overload. This suggests that the approach to frail older adult patients in hospitalization areas is alarmingly insufficient and is reflected in a critical gap in the training and development of specialized geriatric practices. The lack of adequate knowledge about the complexities and specific needs of this vulnerable population results in suboptimal care, prolonged hospital stays, and an increase in complication and readmission rates, not only due to the disease but also because of the overlooked social context. This deficiency highlights the urgent need to prioritize the comprehensive management of older adults across all specialties and geriatrics, promoting more robust training for healthcare professionals and the development of specific protocols that ensure integrated, safe, and dignified care.